TRAINING ON DURIAN CULTIVATION AND MAINTENANCETHROUGH HYDROCULTURE TECHNIQUES INWARUNGPRING VILLAGE, PEMALANG: PELATIHAN BUDIDAYA DAN PEMELIHARAAN TANAMANDURIAN MELALUI TEKNIK HIDROKULASIDI DESA WARUNGPRING PEMALANG - Fatchurohman; Fariha Dwi Kamala; Dimas Setiaji Prabowo; Faiza Alfa Khasanah (PT. ROCE WISDOM ACEH, 2025)
Empowering village communities is a strategic effort to increase the capacity ofindividuals or groups so they can be independent and develop local potential.Warungpring Village, which has great potential in durian cultivation, faces challengesin utilizing this potential due to limited community knowledge and skills regardingappropriate cultivation techniques. This research aims to increase the capacity of theWarungpring Village community in cultivating durian through hydroculationtechniques and good maintenance of durian plants. This empowerment program isexpected to help the community utilize durian's potential optimally and increase theirincome. Community service activities were carried out by UIN KKN student K.HAbdurrahman Wahid Pekalongan in Warungpring Village on August 15 2024. Themethod used included training with three stages: planning, implementation andevaluation. Participants are given knowledge about shoot grafting, grafting andhydroculation techniques, as well as practicing durian planting. The evaluation showsthat the availability of supporting technology such as a simple and affordablehydroculation system makes it easier for farmers to apply this technique. The prospectof higher profits from hydroculated durian cultivation attracts farmers' interest intaking part in the outreach. The availability of quality durian seeds that are suitablefor the hydroculation system facilitates the socialization process, but faces challengesin the form of low participation from residents who live far from the activity location.The community empowerment program through training in hydroculating duriancultivation and durian plant maintenance can increase the knowledge and skills of theWarungpring Village community.